(untitled) (Dhaka Shishu (Children) Hospital Journal, 2023)
Radiation sterilized human amniotic membrane allografts are used as biological dressing of wounds in rehabilitative surgery. The amniotic membrane is used in many different clinical situations such as: heat burn, chemical burns, diabetic wound/ diabetic foot ulcer, leprotic ulcer, abdominal wall reconstruction, pterigium removal site, peripheral corneal ulcer, in the management of pressure sore, etc.Non-viable lyophilized/oven-dried radiation sterilized amniotic membrane allografts could be processed for utilization as temporary biological dressing of wounds. The allografts used clinically should not be the carriers of germs or a source of infection. Human chorio-amniotic membranes collected for processing as tissue allografts to be used as biological dressings were reported to be contaminated with microorganisms such as species of Staphylococcus, Micrococcus, Bacillus and Pseudomonas.However, oven dried (40ºC) or freeze dried (-50ºC) human amniotic membranes were found to be sterilized by irradiation with the dose of 25 kiloGray (kGy) of gamma radiation.Careful screening and selection of tissue donors, proper processing and gamma radiation sterilization of human amniotic membranes minimize the risk of disease transmission to recipients through allografts. DS (Child) H J 2021; 38(1): 49-55